DESCRIPTIVE ANALYSIS OF ISRAELI PRODUCT BOYCOTT ACTION: BETWEEN FATWAS AND THE URGENCY OF COMPLIANCE - Sentosa, Dewi Suryani; Sitepu, Novi Indriyani (International Journal of Kita Kreatif, 2024)
Israel's massacre of civilians in Gaza has angered the global community. This has led to boycott movements in various countries as a form of Palestinian solidarity using market forces. This paper discusses a descriptive analysis of the boycott of Israeli products. The study of boycotting Israeli products uses several literature sources such as research articles, fatwas, and national and international news pages. The results of this paper show the impact of the boycott made various companies affiliated with Israel suffer losses. In addition, boycotts have an impact on layoffs. While the greatest abominations and destruction have occurred throughout human history. The Indonesian Ulema Council has issued a fatwa in support of this boycott, which must be obeyed by local Muslims due to the fatwa's high position and Allah's word calling for obedience to the leader. This paper can be useful for scholars of Islamic economics to add insight